2019
DOI: 10.1177/1074840719889967
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Dyadic Symptom Appraisal With Physical and Mental Health Over Time in Care Dyads Living With Lung Cancer

Abstract: The study examined the association between changes in dyadic symptom appraisal with changes in physical and mental health of 109 family care dyads living with lung cancer over 12 months. Multilevel modeling was used to analyze both aggregate and time-varying associations of dyadic symptom appraisal with dyadic health. Patients had significantly worse physical health compared with their care partner; care partners had significantly worse mental health compared with patients. In general, greater incongruent symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 57 publications
(86 reference statements)
1
24
0
1
Order By: Relevance
“…See Table 5 for extensions of each method as well as cited examples of each. 12,14,26,29,30,[40][41][42][43][44][45][46][47]…”
Section: Extensions Of the Modelsmentioning
confidence: 99%
“…See Table 5 for extensions of each method as well as cited examples of each. 12,14,26,29,30,[40][41][42][43][44][45][46][47]…”
Section: Extensions Of the Modelsmentioning
confidence: 99%
“…As the model focus on the transactional and interdependent nature between couples facing chronic illness, it is widely applied to research on dyadic perspective of illness (Checton, Magsamen‐Conrad, Venetis, & Greene, 2014; Li & Loke, 2015). Previous studies have supported this model that dyadic appraisal and DC both play important roles in dyadic mental health (Gellert et al, 2018; Helgeson et al, 2019; Lyons & Lee, 2020; Lyons et al, 2016).…”
Section: Introductionmentioning
confidence: 71%
“…Theoretical and practical studies indicated that chronic disease, such as cancer and heart failure, can be viewed as a dyad event, which affects the physical, psychological, and social functions of patients and their spouses (Helgeson, Jakubiak, Van Vleet, & Zajdel, 2017). Dyadic appraisal of disease and its related problems play an important role in this process (Lyons & Lee, 2020). Shared dyadic appraisal can promote patients and spouses to participate in disease management behaviour together to deal with the dyad pressure caused by disease and then promote dyadic health (Lyons, Miller, & McCarthy, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, effective symptom recognition and management are vital to preventing costly and unnecessary hospitalizations (Goldberg et al, 2010;Lyons, Sadowski & Lee, 2020;Zhang & Siminoff, 2003). Similar appraisal of the illness within the care dyad has been found to increase the dyad's ability to collaborate and jointly manage the illness together, cope as a unit, and experience better outcomes (Acitelli & Badr, 2005;Berg et al, 2008;Lee et al, 2017;Lehman et al, 2011;Li & Loke, 2014;, 2020aMerz et al, 2011;Trief et al, 2004;Zhang & Siminoff, 2003). Without first examining how members of the care dyad converge or diverge in their appraisal of the illness, however, an important part of illness management is overlooked that may hinder the design of effective dyadic interventions to improve clinical and familial outcomes.…”
mentioning
confidence: 92%